Social media marketing strategies for SMEs in Indonesia: A systematic literature review - Fajar Adi Prakoso; Nurul Sriminarti (Jurnal Bisnis dan Kewirausahaan, 2026)
The rapid digital transformation in Indonesia has established social media marketing as a key tool for enhancing the competitiveness and performance of Small and Medium Enterprises (SMEs). This study conducts a systematic literature review using Scopus-indexed articles published from 2016 to 2025, with an exclusive focus on Indonesian SMEs. The objective is to synthesize empirical evidence, highlighting strategic patterns that contribute to the success of social media marketing. This review follows the PRISMA protocol, which encompasses article selection, screening, eligibility assessment, and thematic synthesis. The 7 studies reviewed cover various sectors such as food and beverages, retail, and the creative industries. Findings indicate that social media marketing significantly enhances brand awareness, customer engagement, and innovation capacity, particularly when integrated with an entrepreneurial orientation and digital literacy. Studies consistently show that SMEs utilizing social media for content marketing, crowdsourcing, and customer relationship management achieve higher marketing performance and sustainable growth. However, this review also identifies persistent barriers, including limited financial resources, inadequate technological skills, and strategic misalignment between digital initiatives and organizational goals. Practitioners are advised to design targeted training programs, financial incentives, and collaborative ecosystems that strengthen SMEs’ digital competitiveness. Future empirical studies are expected to integrate cross-sector and regional comparisons to capture Indonesia’s diverse SME landscape and support evidence-based policy development.